Germany : Financial Sector Assessment Program-Technical Note-Crisis Management and Financial Safety Nets. (IMF Staff Country Reports; Country Report, 2022)
Much progress on resolution planning and preparedness has been achieved since the last FSAP in 2016. Germany's resolution planning is well advanced, with resolution powers broadly in line with best practice and well-developed internal resolution processes. However, the large weight of Less Significant Institutions (LSIs) in Germany's financial sector calls for further progress on planning for crisis management for smaller banks and the institutional protection schemes (IPSs) of which they are members.